Analisis Tekno-Ekonomi Pengaruh Suhu Curing terhadap Performa Mekanik Komposit Sandwich Carbon Fiber/PVC Foam: Tinjauan Sistematis dan Perspektif Efisiensi Biaya - Arya Syahputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
Abstract This study presents a Systematic Literature Review (SLR) that integrates techno-economic analysis of curing temperature variations on the mechanical properties and failure behavior of carbon fiber sandwich composites with polyvinyl chloride (PVC) foam cores. The systematic review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol with structured searches across the Scopus, Web of Science, and Google Scholar databases, using keyword combinations: "curing temperature," "carbon fiber sandwich composite," "PVC foam," "mechanical properties," and "techno-economic analysis." Of 147 identified articles, 19 studies met the inclusion criteria and were analyzed in depth. Composite materials are widely applied in engineering applications due to their superior strength-to-weight ratio; however, manufacturing process parameters such as curing temperature critically influence both structural performance and production cost efficiency. The objective of this study is to synthesize the latest scientific evidence and determine the optimal curing temperature that maximizes mechanical performance while considering the associated energy consumption costs and economic implications of material failure prevention. Experimental validation was carried out using specimens fabricated via the vacuum bagging method, subjected to curing temperatures of 70°C, 80°C, and no curing (room temperature). Flexural testing was performed using the three-point bending method in accordance with ASTM C393 standards. The synthesis of systematic review findings and experimental validation demonstrates that curing at 80°C yields the highest flexural strength (48.35 MPa) and elastic modulus (67.03 GPa), representing a 60.8% improvement over uncured specimens. From an engineering economics perspective, the additional energy costs of curing at 80°C are substantially offset by reduced failure risk, lower maintenance costs, and an extended service life of the composite structure. These findings support the adoption of 80°C curing as the economically optimal manufacturing condition for carbon fiber/PVC foam sandwich composites.